Biomechanical properties of ascending aorta and pulmonary trunk in pigs and humans - Li, Wen-Chun; Yu, Ming-Hua; Zhang, Hong-Mei; Wang, Han-Qin; Xi, Gang-Ming; Yao, Bo-Chun; Deng, Zhao-Hong; Zeng, Yan-Jun (Xenotransplantation (Københaven), 2008)
:  Background:  This study aims to obtain the biomechanical properties of ascending aorta and pulmonary trunk between healthy humans and pigs of different months, so as to provide necessary biomechanical experimental basis for anastomosing blood vessel in pig‐to‐human heart xenotransplantation. Methods:  Ascending aorta and pulmonary trunks of the six deceased donors (male 4, female 2) and 42 Chinese Hubei white pigs aged 1–7 months were performed biomechanical test. The blood vessel was given periodic permanent loading and unloading, and repeated force‐deformation data were obtained. The elastic properties of the blood vessels were obtained by curve from experimental data. Results:  The biomechanical material constant of ascending aorta and pulmonary trunk of pigs did not increase with the increase of age (F = 14.569, P = 0.126). The biomechanical material constant of humans was basically similar to that of pigs aged 1–7 months (F = 12.264, P = 0.225). The elastic modulus was the biggest in pigs aged 7 months in comparison with that in other ages (F = 27.425, P = 0.032). There was no significant difference of elastic modulus of corresponding blood vessel between humans and pigs of different months (F = 17.328, P = 0.215). Conclusions:  Our present study suggests that there was no significant difference of elastic properties of ascending aorta and pulmonary trunks between humans and pigs. From biomechanical aspects, anastomosis of corresponding ascending aorta and pulmonary trunks in the process of pig‐to‐human heart xenotransplantation may be feasible.